Continuous-flow isotope ratio mass spectrometry method for carbon and hydrogen isotope measurements on atmospheric methane - M. Brass (Atmospheric Measurement Techniques, 2010)
We describe a continuous-flow isotope ratio mass spectrometry (CF-IRMS) technique for high-precision δD and δ13C measurements of atmospheric methane on 40 mL air samples. CH4 is separated from other air components by utilizing purely physical processes based on temperature, time and mechanical valve switching. Chemical agents are avoided. Trace amounts of interfering compounds can be separated by gas chromatography after pre-concentration of the CH4 sample. The purified sample is then either combusted to CO2 or pyrolyzed to H2 for stable isotope measurement. Apart from connecting samples and refilling liquid nitrogen as coolant the system is fully automated and allows an unobserved, continuous analysis of samples. The analytical system has been used for analysis of air samples with CH4 mixing ratios between ~100 and ~10 000 ppb, for higher mixing ratios samples usually have to be diluted.